Meteorological and ozone sounding experience during a strong foehn event a MAP case study - Martin Piringer; Kathrin Baumann; Ulrike Pechinger; Siegfried Vogt (Meteorologische Zeitschrift, 2001)
Within the Mesoscale Alpine Programme MAP, the Rhine valley ozone study ROM was conducted, putting additional instrumentation in the area just south of the Lake of Constance. The vertical structure and the temporal evolution of the planetary boundary layer (PBL) and the ozone concentrations during foehn episodes were observed by using a tethersonde system carrying up to three meteorological and up to two ozone sondes simultaneously, a sonde mounted on the Pfaender cable car, a sodar as well as an ultrasonic anemometer and one conventional ground-based meteorological station. A wind-temperature radar (WTR) was operated near Rankweil, about 20 km south. The potential of the primarily vertical sounding devices, especially of the new tethered balloon system and the cable car sonde, to detect in detail the complex meteorological and ozone structure of the boundary layer is demonstrated for the strong foehn case on 24 October 1999. The data set highlights a lot of interesting features like the often occurring lifting of the foehn flow above a prevailing cold air pool when propagating out of the Rhine valley into the Alpine foreland, giving rise to strong vertical gradients of ozone, temperature and humidity as well as pronounced vertical wind shear. The WTR gives insight how far south the near-surface cold air pool may reach during foehn. Im Rahmen des ,,Mesoscale Alpine Programmes“ MAP wurde die Rheintal-Ozonstudie durchgeführt. Dabei wurden im österreichischen Gebiet südlich des Bodensees zusätzliche Instrumente positioniert. Die Vertikalstruktur und die zeitliche Entwicklung der Grenzschicht sowie der Ozonkonzentrationen während Föhnepisoden wurden mittels Fesselballonsystem mit bis zu drei meteorologischen und zwei Ozonsonden, einer Seilbahnsonde am Pfänder, einem Sodar, einem Ultraschallanemometer und einer konventionellen meteorologischen Bodenstation gemessen. Etwa 20 km südlich, in der Nähe von Rankweil, wurde ein Wind-Temperatur-Radar betrieben. Die Fähigkeit der Vertikalsondierungssysteme, besonders des neuen Fesselballonsystems und der Seilbahnsonde, die komplexe meteorologische und Ozonstruktur der Grenzschicht im Detail zu erfassen, wird für das markante Föhnereignis am 24. Oktober 1999 demonstriert. Der Datensatz zeigt eine Reihe interessanter Einzelheiten wie das Abheben der Föhnströmung über einer Kaltluftschicht im Bereich der Mündung des Rheintals in das Alpenvorland, was zu starken vertikalen Gradienten des Ozons, der Temperatur und Feuchte und zu großer vertikaler Windscherung führt. Die WTR-Messungen zeigen, wie weit südlich die bodennahe Kaltluftschicht bei Föhn reichen kann.